2012
DOI: 10.1021/jm301048a
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of (2S,3R)-N-[2-(Pyridin-3-ylmethyl)-1-azabicyclo[2.2.2]oct-3-yl]benzo[b]furan-2-carboxamide (TC-5619), a Selective α7 Nicotinic Acetylcholine Receptor Agonist, for the Treatment of Cognitive Disorders

Abstract: (2S,3R)-N-[2-(Pyridin-3-ylmethyl)-1-azabicyclo[2.2.2]oct-3-yl]benzo[b]furan-2-carboxamide (7a, TC-5619), a novel selective agonist of the α7 neuronal nicotinic acetylcholine receptor, has been identified as a promising drug candidate for the treatment of cognitive impairment associated with neurological disorders. 7a demonstrated more than a thousand-fold separation between the affinities for the α7 and α4β2 receptor subtypes and had no detectable effects on muscle or ganglionic nicotinic receptor subtypes, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 70 publications
0
42
0
Order By: Relevance
“…Preclinical studies have demonstrated the efficacy of several a7 nAChR agonists in an N40 sensory gating model (Hashimoto et al, 2005;Simosky et al, 2008;Wildeboer-Andrud and Stevens, 2011), in particular ABT-107 (Radek et al, 2012). Other molecules such as TC-5619, SSR-180711, A-582941, or encenicline also demonstrated efficacy in cognitive models (Pichat et al, 2007;Tietje et al, 2008;Mazurov et al, 2012;Prickaerts et al, 2012). Although application of an a7 nAChR agonist alone was ineffective in a DBA/2 mouse model of sensorimotor gating (prepulse inhibition), it increased the effects of haloperidol or risperidone (Kohlhaas et al, 2012).…”
Section: B Schizophreniamentioning
confidence: 99%
“…Preclinical studies have demonstrated the efficacy of several a7 nAChR agonists in an N40 sensory gating model (Hashimoto et al, 2005;Simosky et al, 2008;Wildeboer-Andrud and Stevens, 2011), in particular ABT-107 (Radek et al, 2012). Other molecules such as TC-5619, SSR-180711, A-582941, or encenicline also demonstrated efficacy in cognitive models (Pichat et al, 2007;Tietje et al, 2008;Mazurov et al, 2012;Prickaerts et al, 2012). Although application of an a7 nAChR agonist alone was ineffective in a DBA/2 mouse model of sensorimotor gating (prepulse inhibition), it increased the effects of haloperidol or risperidone (Kohlhaas et al, 2012).…”
Section: B Schizophreniamentioning
confidence: 99%
“…Despite the limited number of compounds described as α7 nAChR PAMs, several of them have advanced 1,3-diphenylpropan-1-ones as allosteric modulators of α7 nACh receptors with analgesic and antioxidant properties Manuel Criado* ,1 , Beatriz Balsera 2 , José Mulet 1 , Salvador Sala 1 , Francisco Sala 1 , Roberto de la Torre-Martínez 3 toward clinical development [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Within the families of α7 nAChR allosteric modulators, a series of cyclopentatetrahydroquinoline-8-sulfonamide derivatives is worth mentioning, since they showed different pharmacological properties depending on the nature, number and position of certain substituents [9,24].…”
mentioning
confidence: 99%
“…Highly potent and selective α7 nAChR agonist TC-5619 (21) [151] (Fig. 6) binds to the α7 nAChR both in rat hippocampal membranes and in a HEK293 cell line coexpressing human α7 and RIC3 cDNAs with a K i of 1 nM.…”
Section: α7 Nachr Agonists For Schizophreniamentioning
confidence: 99%